Edukasi Pencegahan dan Pemeriksaan Malaria pada Ibu Hamil - Muji Lestari; Fitrah A Iriani; Fachry Amal (Jurnal Inovasi, Pemberdayaan dan Pengabdian Masyarakat, 2022)
Malaria is still a public health problem. Malaria can attack anyone from infants to the elderly, even pregnant women. Community service is carried out by means of counseling, distribution of leaflets and malaria examination using the RDT method. Based on the results of the post test carried out, it showed that the knowledge of the target community/pregnant women increased compared to before the service activities were carried out, this was illustrated by the answers of the target audience on the questionnaire sheets that had been distributed and filled out. The results of service activities at the Genyem Health Center can increase the independence of the community/pregnant women to take preventive measures, recognize the signs and symptoms of malaria. This independent behavior is something that is very important for citizens to do. Education has been carried out to the public/pregnant women about malaria prevention and malaria examination in pregnant women. Implications for civil servants. Community service activities can increase the knowledge of the target audience about malaria prevention.